2018
DOI: 10.1210/js.2018-00226
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Pathology and Gene Expression in Acromegalic Cats

Abstract: The prevalence of GH-secreting pituitary tumors in domestic cats (Felis catus) is 10-fold greater than in humans. The predominant inhibitory receptors of GH-secreting pituitary tumors are somatostatin receptors (SSTRs) and D2 dopamine receptor (DRD2). The expression of these receptors is associated with the response to somatostatin analog and dopamine agonist treatment in human patients with acromegaly. The aim of this study was to describe pathological features of pituitaries from domestic cats with acromegal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 56 publications
2
30
0
Order By: Relevance
“…24,25 Response to cabergoline therapy can also vary depending on prior treatments, alternative splicing of DRD2 mRNA, magnitude of dopamine receptor expression at the protein level or defective signalling pathways downstream of DR2 stimulation. [26][27][28][29] It has been reported that cats with hypersomatotropism have a moderate negative correlation between DRD2 expression and pituitary size 7 . That data suggests that pituitary size might be related to cabergoline responsiveness, but there was no difference of pituitary size between those who experienced an IGF1 decrease versus those who did not in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24,25 Response to cabergoline therapy can also vary depending on prior treatments, alternative splicing of DRD2 mRNA, magnitude of dopamine receptor expression at the protein level or defective signalling pathways downstream of DR2 stimulation. [26][27][28][29] It has been reported that cats with hypersomatotropism have a moderate negative correlation between DRD2 expression and pituitary size 7 . That data suggests that pituitary size might be related to cabergoline responsiveness, but there was no difference of pituitary size between those who experienced an IGF1 decrease versus those who did not in this study.…”
Section: Discussionmentioning
confidence: 99%
“…6 As cats with HST have pituitary expression of D2R, therapy with a DRA might result in improved GH control and therefore diabetic control. 7 Cabergoline and bromocriptine are DRAs with high affinity for D2R in rats and monkeys 8,9 . Cabergoline is the D2R-specific DRA with more favourable properties, having a longer action of duration and thus requires less frequent dosing, is better tolerated and exhibits increased insulin sensitising effects independent of GH reduction compared to bromocriptine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have established that the prevalence of acromegaly (or hypersomatotropism, HST) in the domestic cat ( Felis catus ) are approximately ten times that seen in the human population, and is a primary cause of diabetes mellitus in 25% of diabetic cats [ 14 ]. Molecular and histological analyses of these feline pituitary tumours reveals expression of therapeutic targets, such as somatostatin and dopamine receptors [ 15 ]. However, the natriuretic peptide system in feline pituitaries has yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Hypersomatotropism (HST) is defined as an excess secretion of growth hormone (GH) typically caused by a pituitary somatotroph adenoma; however, some cases of pituitary acidophilic hyperplasia have also been described. 1 In cats, GH-producing pituitary tumours are the most common type of pituitary tumour, with a prevalence 10-fold greater than humans. 2 Acromegaly is the clinical syndrome that develops from GH overproduction in adults.…”
Section: Introductionmentioning
confidence: 99%